2002
DOI: 10.1016/s0736-0266(01)00106-1
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal knee joint position sense in individuals with patellofemoral pain syndrome

Abstract: The purpose of this cross-sectional study was to compare knee joint position sense (JPS) in 20 individuals with and 20 without patellofemoral pain syndrome (PFPS). Five active tests with ipsilateral limb matching responses were performed at 20" and 60" flexion under non-weightbearing conditions, and at 40" flexion under uni-and bi-lateral weightbearing conditions. The response errors were calculated as the difference between each target and response position (accuracy) and the standard deviation of these diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
144
1
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(166 citation statements)
references
References 31 publications
9
144
1
9
Order By: Relevance
“…8,9 However, a more recent study compared JPS in 20 PFPS patients and 20 matched healthy control subjects. 10 The results showed that the PFPS patients were significantly less accurate and less consistent than the healthy control subjects.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…8,9 However, a more recent study compared JPS in 20 PFPS patients and 20 matched healthy control subjects. 10 The results showed that the PFPS patients were significantly less accurate and less consistent than the healthy control subjects.…”
Section: Introductionmentioning
confidence: 91%
“…20,21 These target angles were also chosen to enable comparability with other previous work in this area. 10,22 The target angles and type of test were conducted in random order to prevent the confounding influence of learning effects. For PAR, the lever arm passively extended the limb at an angular velocity of 28/s to limit any reflexive muscle contractions.…”
Section: Measurement Of Proprioceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patellofemoral pain syndrome (PPS) frequently affects female athletes, the female sedentary population, and young women are most affected [1][2][3] . This syndrome is present in approximately 25% of orthopedic diagnoses 4 and is defined as a pain at the front of the knee and/or rear of the patella [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Although the etiological factors of PPS are not well-defined, some authors have pointed towards biomechanical abnormalities in the lower limbs as the main cause [1][2][3] . Among the biomechanical factors most frequently correlated with the development of PPS, dynamic disequilibrium stands out 1,2 .…”
Section: Introductionmentioning
confidence: 99%